Trans-resveratrol reduces visible signs of skin ageing in healthy adult females over 40: an 8-week randomized placebo-controlled trial - Rao, Amanda; Briskey, David; Roche, Georgia; Tremblay, Annie; Da Silva Pinto, Marcia; Tompkins, Thomas A. (Frontiers in Aging, 2025)
IntroductionThis double-blind, randomised, placebo-controlled clinical study evaluated the effects of trans-resveratrol on skin health. To date, and to the best of our knowledge, no study has tested trans-resveratrol as the only active ingredient, orally or topically, for improving skin parameters in humans. Therefore, the aim of this study was to investigate the effects of trans-resveratrol on skin health and visible signs of ageing, when administered orally and/or applied topically to the face.MethodsHealthy females aged 40 years and older were randomly assigned to one of four groups: placebo oral and topical (P/P Group), trans-resveratrol oral and placebo topical (A/P Group), placebo oral and trans-resveratrol topical (P/A Group), and trans-resveratrol oral and topical (A/A Group). Participants were instructed to take one capsule (75 mg trans-resveratrol) and apply 1 g of cream (1.5% trans-resveratrol) twice daily for 8 weeks. Outcome measures included wrinkle assessment, skin age, temperature, pore size, forehead lines, glabellar lines, Crow’s feet, nasolabial folds, pigmentation, sebum levels, moisture, and elasticity, along with a self-assessment questionnaire, serum trans-resveratrol concentrations, and safety.ResultsOut of 134 participants enrolled, 122 completed the study. Results indicated significantly reduced wrinkle scores in the A/A Group compared to the P/P Group at week 8. All treatment groups showed increased sebum levels, with the active topical groups (P/A and A/A Groups) having significantly higher U-zone sebum at week 8 compared to placebo topical groups (P/P and A/P Groups). No significant differences were found in other skin parameters. Serum trans-resveratrol conjugate levels increased significantly in the A/P and A/A Groups at week 4 and 8. All trial products were shown to be safe with minimal and only mild adverse events recorded in every group.ConclusionOral and topical trans-resveratrol treatment can help improve skin health parameters. When taken orally and applied topically, trans-resveratrol was effective at wrinkle reduction, and when applied topically, it increased sebum levels.Clinical Trial Registrationidentifier ACTRN12621000709842.